Black Gold: Aboriginal People on the Goldfields of Victoria, 1850-1870 - Cahir, Fred (ANU Press, 2012)
Fred Cahir tells the story about the magnitude of Aboriginal involvement on the Victorian goldfields in the middle of the nineteenth century. The first history of Aboriginal-white interaction on the Victorian goldfields, Black Gold offers new insights on one of the great epochs in Australian and world history-the gold story. In vivid detail it describes how Aboriginal people often figured significantly in the search for gold and documents the devastating social impact of gold mining on Victorian Aboriginal communities. It reveals the complexity of their involvement from passive presence, to active discovery, to shunning the goldfields. This detailed examination of Aboriginal people on the goldfields of Victoria provides striking evidence which demonstrates that Aboriginal people participated in gold mining and interacted with non-Aboriginal people in a range of hitherto neglected ways. Running through this book are themes of Aboriginal empowerment, identity, integration, resistance, social disruption and communication.